Evaluation of Kubuqi Desert Wind Erosion Prevention Service and drivers of the actual wind erosion studies Based on RWEQ Model from 2000 to 2022 - Yinchao Chai; Hejun Zuo; Min Yan; Tao Zuo; Yu Yan (PLoS ONE, 2025)
Ecosystem service research is essential to identify the contribution of the ecosystem to human welfare. As an important ecological barrier zone, the Kubuqi Desert supports the use of a crucial wind erosion prevention service (WEPS) to improve the ecological environment quality. Based on the Revised Wind Erosion Equation (RWEQ) model, the spatial and temporal changes of WEPS in the Kubuqi Desert region were simulated from 2000 to 2022, and the impacts and interactions of natural and socio-economic factors including numerical and typological variables on the spatial pattern of wind and sand control services in the region were analyzed by using geographical detector. From 2000 to 2022, the total WEPS provided in the Kubuqi Desert ranged from 0.35 × 107 t to 1.26 × 107 t. The average WEPS per unit area was between 0.19 kg m-2 to 0.68 kg m-2.WEPS has a higher spatial distribution in the east and a lower spatial distribution in the west. Soil type was the most important driver of the actual wind erosion (SL), with vegetation cover, elevation, mean annual temperature, mean annual wind speed, and mean annual precipitation as the main drivers, and population size and GDP as secondary drivers. The interaction analysis showed that the interaction of weather factor, vegetation factor and soil factor is the dominant factor influencing the amount of soil wind erosion in the Kubuqi Desert.